MANAGEMENT OF SEGMENTAL FRACTURE OF TIBIA TREATED BY ILIZAROV EXTERNAL FIXATION - Makhdoom, Asad ullah; Shaikh, Babar Jan; Baloch, Raheel Akbar; Malah, Hamid Raza; Tunio, Zamir Hussain; Jokhio, Muhammad Faraz (Journal of Ayub Medical College Abbottabad, 2020)
Background: Tibial shaft segmental fractures are mostly occurring due to a high’‘energy trauma that produces a severe soft’‘tissue injury and resulting an excessive frequency of open and closed segmental fractures, and needs effective stable management. The objective of the study was to evaluate the functional outcome and union time in segmental tibial fracture treated with Ilizarov method. Methods: This prospective Qausi-experimental study was carried out from March 2014 to February 2018. Total 45 patients were included (36 males, 09 females) with a mean age of 30 years (range 20-50) with segmental tibial fractures either closed or open without any gender bar, were stabilized with an Ilizarov method. Functional outcome and bone union was assessed by ASAMI criteria. Patients were followed up to 18 months. SPSS-21.0 was used to calculate the descriptive statistics and t-test of difference between union time in open and close fractures. Results: According to Gustilo classification for open fractures, there were Grade IIIA 21 (67.7%), Grade IIIB 10 (32.2%). According to AO classification for closed fractures; 42-C1 type fractures were 5 (35.7%), 42-C2 was 6 (42.8%), 42-C3 was 3 (21.4%). Based on ASAMI criteria for bone assessment; excellent results in 26 (57.8%), good results in 16 (35.5%) and fair results in 3 (6.6%) and functional outcome was 29 (64.4%) excellent, 12 (26.6%) good and 4 (8.8%) fair was obtained. Union time difference was examined using t-statistics and score of p was greater than 0.05. This result was expected as an average time of union was almost similar in both groups, i.e., 19.83, ±11.92 in close and 20.73, ±9.09 within an open group. Overall, the union time was minimum 10.86, maximum 45.14, and median was 20.29. Conclusion: Ilizarov is an effective method for the stabilization of segmental tibial fractures because the method allows close reduction without extensive soft tissue damage and is efficient for the stabilization of short distal segmental fractures of the tibia. Keywords: Tibia fractures; Segmental; Ilizarov external fixator